The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1120/jacmp.v16i2.5201
|View full text |Cite
|
Sign up to set email alerts
|

Initial clinical experience with a radiation oncology dedicated open 1.0T MR‐simulation

Abstract: The purpose of this study was to describe our experience with 1.0T MR‐SIM including characterization, quality assurance (QA) program, and features necessary for treatment planning. Staffing, safety, and patient screening procedures were developed. Utilization of an external laser positioning system (ELPS) and MR‐compatible couchtop were illustrated. Spatial and volumetric analyses were conducted between CT‐SIM and MR‐SIM using a stereotactic QA phantom with known landmarks and volumes. Magnetic field inhomogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 56 publications
(71 reference statements)
0
19
0
Order By: Relevance
“…Using a 1.0 T Panorama high‐field open vertical‐bore system (Philips Medical Systems, Best, The Netherlands), a vendor‐supplied 3D distortion phantom consisting of docusate sodium capsules within a foam structure (17) was scanned using a 3D T1 spoiled gradient echo sequence (voxel size 0.938×0.938×2mm3,450×450×400mm3 FOV, 385 Hz/pixel, TE/TR/flip angle: 3.77 ms/30 ms/60°, 3D correction algorithm applied). ACT of this phantom was also acquired.…”
Section: Methodsmentioning
confidence: 99%
“…Using a 1.0 T Panorama high‐field open vertical‐bore system (Philips Medical Systems, Best, The Netherlands), a vendor‐supplied 3D distortion phantom consisting of docusate sodium capsules within a foam structure (17) was scanned using a 3D T1 spoiled gradient echo sequence (voxel size 0.938×0.938×2mm3,450×450×400mm3 FOV, 385 Hz/pixel, TE/TR/flip angle: 3.77 ms/30 ms/60°, 3D correction algorithm applied). ACT of this phantom was also acquired.…”
Section: Methodsmentioning
confidence: 99%
“…First, images were generated by taking the maximum intensity projection of each of all 13 slices for each scan, which is consistent with our clinical protocol. 15 Control point detection was then conducted on each image with a combination of masking and thresholding, while a connectivity algorithm was used to further separate control points from increased noise at the field boundaries. The x and y positions (horizontal and vertical axes, respectively) were determined by finding the centroid of each control point and were compared to a binary template generated from the factory schematic of the phantom.…”
Section: C Image Analysismentioning
confidence: 99%
“…We have previously reported on our magnet's B 0 field inhomogeneity and found that it was within American College of Radiology guidelines. 15 This technical note focuses on the technical characterization of gradient nonlinearity (GNL) for large fields of view (FOVs), develops and evaluates a correction scheme, and then quantifies the temporal stability of the measurements for a clinically available MR-SIM system. GNL is the focus of this work, because it is one of the dominant sources of image distortion 16,17 and is insensitive to the acquisition sequence.…”
Section: Introductionmentioning
confidence: 99%
“…Coronal acquisitions are performed to ensure high spatial resolution in the superior–inferior direction where liver motion is dominant (3) . 4D MRIs were acquired on a 1.0T Philips Panorama High Field Open (HFO) magnetic resonance system (RT Oncology Configuration, v3.5.2, Philips Medical Systems, Cleveland, OH), which has been described in detail elsewhere 16 , 20 . Respiratory triggering was performed based on a signal derived from an air‐filled cushion placed on the abdomen that was used as an external surrogate.…”
Section: Methodsmentioning
confidence: 99%